UNDERSTANDING PUBLIC COMPLIANCE WITH COVID-19 HEALTH PROTOCOLS IN INDONESIA: A CROSS-SECTIONAL STUDY - Oktavia, Nada Karisma; Boerman, Baequni; Nasir, Narila Mutia; Samara, Shafira Salsabila (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2024)
Background: The Coronavirus Disease 2019 has become a global pandemic, affecting many countries, including Indonesia. The number of COVID-19 cases in Indonesia, particularly in Jakarta, continues to increase. Purpose: This study aimed to identify the factors influencing compliance with the COVID-19 prevention protocol among Jakarta's residents. Methods: An accidental sampling technique was used in this study, with the calculation of hypothesis testing of the difference between two proportions, resulting in a total sample of 440 respondents. Data was collected through an online survey using Google Forms. Results: The study found that education level (p-value=0.003; OR=1.818), knowledge (p-value=0.01; OR=6.669), attitude (p-value=0.01; OR=7.789), perception of vulnerability to COVID-19 (p-value=0.01; OR=3.307), social support (p-value=0.01; OR=3.733), and supervision (p-value=0.01; OR=3.435) had a significant relationship with compliance with the COVID-19 prevention protocol. However, facilities and infrastructure (p-value=0.341; OR=0.453) had no significant relationship with compliance. From the odds ratio data, knowledge and attitude significantly influence adherence to COVID-19 preventive measures. Individuals well-informed about COVID-19 are 6.6 times more likely to comply, and a positive attitude increases this likelihood by 7.8-fold. This underscores the strong link between awareness and adherence to recommended protocols. Conclusion: This study highlights the importance of understanding the factors affecting adherence to COVID-19 prevention protocols. It guides policymakers and public health professionals in devising effective strategies to curb the spread of the disease.